Analisis Kualitas Jaringan WLAN pada Bank Mandiri Area Palembang Sudirman - Siti Nurdianah (Jurnal Jaringan Komputer dan Keamanan, 2021)
Along with the rapid development of the internet and information technology, especially in the field of computer networks, the quality of network services has become a very important factor in supporting organizational operational activities. Bank Mandiri Palembang Sudirman Area has utilized Wireless Local Area Network (WLAN) to support office activities. This study aims to analyze the quality of WLAN network performance in Bank Mandiri Palembang Sudirman Area based on Quality of Service (QoS) parameters, namely bandwidth, packet loss, and delay. The research method used is action research which includes the stages of diagnosis, action planning, action implementation, evaluation, and learning. Measurements were carried out using Axence NetTools v5 software for five days during peak hours. The results of the study indicate that the quality of the WLAN network in Bank Mandiri Palembang Sudirman Area is in the very good category based on the TIPHON standard, with a packet loss of 0% and an average delay value below 150 ms. In addition, the application of the Per Connection Queue (PCQ) method has been proven to be able to reduce the delay value from 32 ms to 8 ms and packet loss from 1.5% to 0%. Thus, the implementation of bandwidth management using the PCQ method is effective in improving the quality of WLAN network performance.